Brand Identity Implementation and Brand Awareness Formation Case Study: Tweely - Muhammad Fikar Ravsanjani; Agus Rahayu; Puspo Dewi Dirgantari (Borong Newinera Publisher, 2023)
The rapid growth of the fashion industry has become a unique challenge for founders of fashion companies in Indonesia. This research aims to understand how Tweely implements brand identity in forming brand awareness for Tweely. Brand identity itself is an element of a brand that encompasses brand as an organization, brand as a product, brand as a person, and brand as a symbol, containing the values of a product in the company for consumers to understand. In brand awareness, there are levels that start from unaware of the brand, brand recognition, brand recall, and top of mind. This research uses a qualitative approach with a descriptive case study research method. Interviews were conducted with two sources, namely the owner of Tweely and the Tweely Marketing team. The results of this research indicate that by implementing brand identity in the company's products or brand, brand awareness can be built by maintaining product quality, marketing campaigns, and also social media interactions that influence engagement.